2022
DOI: 10.1037/fam0000875
|View full text |Cite
|
Sign up to set email alerts
|

Children’s well-being in sole and joint physical custody families.

Abstract: Joint physical custody (JPC), a parental care arrangement in which children live with each parent about equally after separation or divorce, is an increasingly common phenomenon in many countries. This is a major shift away from the standard of sole physical custody (SPC), in which children live primarily with one parent (usually their mother) after family dissolution. Although attention to JPC by social scientists is growing, and the effects of this arrangement on children's well-being are the subject of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…However, it must always be submitted to the Family and Minors Court for approval or hearing, if necessary, except family circumstances in which it is not possible or when it is not in the best interests of the child. Notwithstanding this, household arrangements remain asymmetric as in other western countries [33,39]. Even with equivalent groups of sole and joint psychical custody, the distribution of the number of days with fewer days spent with the father follows that found in earlier studies Based on attachment to the mothers, children under three are traditionally in sole custody, spending fewer overnights with the father, thus overlooking attachment to fathers or father involvement [14,55].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, it must always be submitted to the Family and Minors Court for approval or hearing, if necessary, except family circumstances in which it is not possible or when it is not in the best interests of the child. Notwithstanding this, household arrangements remain asymmetric as in other western countries [33,39]. Even with equivalent groups of sole and joint psychical custody, the distribution of the number of days with fewer days spent with the father follows that found in earlier studies Based on attachment to the mothers, children under three are traditionally in sole custody, spending fewer overnights with the father, thus overlooking attachment to fathers or father involvement [14,55].…”
Section: Discussionmentioning
confidence: 79%
“…In a large study in Germany, children in joint physical custody presented higher wellbeing when compared to the sole custody group. However, differences in child adjustment disappeared when controlling for parent, child, separation, and quality of family relationship [39]. When high interparental conflict occurs, children from both custody arrangements denote similar levels of mental health problems [37].…”
Section: Child Physical Custodymentioning
confidence: 97%
“…A German study based on a convenience sample (Augustijn 2021a) also showed similar findings: Although SPC children displayed fewer psychosomatic problems than children in sole care models, these differences can at least partly be explained by the selectivity into SPC (e.g., a better parent-child relationship, interestingly especially with the mother rather than the father). Other analyses based on this data also demonstrated that SPC children were better off with regard to other dimensions of well-being (e.g., physical health or school grades) compared to children in sole care models (Steinbach and Augustijn 2021). However, when several control variables were taken into account (e.g., the quality of family relationships), these differences disappeared.…”
Section: Physical Custody Arrangements and Child Adjustmentmentioning
confidence: 51%
“…Compared to two-parent families there are hardly any disadvantages in child well-being (e.g., Hagquist 2016). Furthermore, the reported associations often disappeared when other family characteristics, such as relationship qualities, were taken into account (Steinbach and Augustijn 2021). In other representative studies, there were hardly any differences between the different physical custody arrangements after separation (i.e., SPC vs. sole care models; Hjern et al 2021a).…”
Section: Physical Custody Arrangements and Child Adjustmentmentioning
confidence: 96%
“…As Pruett et al ( 2014 ) summarized, “Critical variables in considering readiness for and the likely impact of overnight schedules include parents’ psychological and social resources, the current nature of parental dynamics—particularly conflict, and the nature and quality of each parent–child relationship prior to separation.” (p. 250). Indeed, accumulating evidence has indicated that the circumstances under which a given physical custody arrangement is practiced—and especially the quality of family relationships—are more important than the custody arrangement itself (see Steinbach & Augustijn, 2021 ; Steinbach et al, 2021 ).…”
Section: Parental Involvement and Parent–child Relationship Following...mentioning
confidence: 99%